Organic Coatings Material for Indoor Ultraviolet Blocking and Thermal Management: A Review - Billy Sopater Maniani; Israel Isack Mirino; Primasari Cahya Wardhani; Pardi Sampe Tola (Nusantara Science and Technology Proceedings, 2023)
Global warming leads to the enhanced greenhouse effect, causing Earth’s average temperature to rise, thus increasing energy use for the air conditioning system and refrigerator. Cooling systems contain ozone-depleting substances (ODS) when released into the atmosphere can contribute to ozone layer depletion, which results in high ultraviolet (UV) transmission. In this context, natural cooling systems have been developed to address this problem, however, they can also be a source of issues. Natural cooling systems utilize passive and low-energy methods to cool indoor spaces, these systems are based on natural phenomena, architectural design, and environmental conditions to maintain comfort in indoor temperature. Optical coating is an effective technique to maintain the indoor temperature. This method involves photothermal activity control by minimizing solar heat gained from infrared radiation absorption and selective reflection of UV radiation. Herein we review the development on organic material for indoor light selective coating, with a focus on lignin fabrication as an active material and its optical properties, namely UV blocking properties.